TRADISI LISAN DODA-IDI SEBAGAI PEMBENTUK KARAKTER ANAK ACEH * (ORAL TRADITION DODA-IDI AS FORMING CHARACTER CHILD ACEH) - Armia - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
This riset as a flashback to the past Acehnese in function of oral tradition in shaping the character of children. The author sees the point of view of character formation of children in Aceh since the early (since the swing). The issue today is (1) deviated character of today's young generation, (2) concerns about the character of the young generation in the future. Based on the above problems, the formulation of the research problem as follows: (1) how the oral tradition-doda idi child Aceh since past. Description of the purpose of this study was to: (1) describe the oral tradition-doda idi as a child character formation, (2) describe the character formed by tradition-doda idi. This research uses descriptive qualitative method. research results is to set (1) How to integrate the values for the formation of character generation in Aceh can be done by (a) selecting poems-doda idi accordance with the value which would integrated, (b) integrated values-doda idi poem that spoken/sung since the swing. (c) provide reinforcement in the positive values contained in the poem doda idi. (d) the child appreciated avoid ambiguous/appreciation can bring negative values for the formation of the character of the child. (e) maintain the oral tradition as a means of creating a creative for the formation of the character of the child. (2) The values of the characters can be integrated in the poems-doda idi is     (a) the character of the love of God and all His creation, (b) self-reliance and responsibility, (c) honesty or trust, diplomatically, (d) respect and polite, (e) generous, like helping each other and mutual assistance, (f) self-confident and intelligent worker, (g) leadership and justice, (h) a good and humble, (i) the character of tolerance, peace and unity.  Key words: oral tradition, doda-idi, character